2022
DOI: 10.1186/s13033-022-00524-z
|View full text |Cite
|
Sign up to set email alerts
|

Networks to strengthen community social capital for suicide prevention in regional Australia: the LifeSpan suicide prevention initiative

Abstract: Introduction Mental health services are fragmented in Australia leading to a priority being placed on whole-of-community approaches and integration. We describe the LifeSpan suicide prevention intervention developed by the Black Dog Institute that draws upon nine evidence-based community-wide strategies. We examined the suicide prevention Collaborative group at each site. We evaluated how the social capital of the community and service providers changed, and how the brokerage roles of the Colla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…When priorities are not aligned, clinicians feel they must compromise, and thus dilute their effectiveness. Change fatigue is being reported, as stakeholders struggle to meet the demands of successive or concurrent projects that pull them in different directions 40,41 . Ad hoc approaches to change set up a context of confusing priorities that can trigger disengagement, tokenistic efforts, or cynicism.…”
Section: Resultsmentioning
confidence: 99%
“…When priorities are not aligned, clinicians feel they must compromise, and thus dilute their effectiveness. Change fatigue is being reported, as stakeholders struggle to meet the demands of successive or concurrent projects that pull them in different directions 40,41 . Ad hoc approaches to change set up a context of confusing priorities that can trigger disengagement, tokenistic efforts, or cynicism.…”
Section: Resultsmentioning
confidence: 99%
“…It could be argued that all these strategies promoted possibilities for learning, growth and development within the broader LifeSpan team, and ultimately may have enhanced healthcare system functioning within each of the sites involved [ 37 ]. Indeed, as identified from our social network survey study of LifeSpan [ 24 ], the site coordinators were empirically identified as the “key players in the networks”, and “were noted to be exceptional people who magnified the benefits of collaboration” (p.1). All in all, the efforts of the LifeSpan coordinators in building a collaborative network in each site was identified as a key success factor for the implementation of LifeSpan [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, as identified from our social network survey study of LifeSpan [ 24 ], the site coordinators were empirically identified as the “key players in the networks”, and “were noted to be exceptional people who magnified the benefits of collaboration” (p.1). All in all, the efforts of the LifeSpan coordinators in building a collaborative network in each site was identified as a key success factor for the implementation of LifeSpan [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations